Management of Biology Learning in Integrating 21st Century Skills at Muhammadiyah High School Special Program Kottabarat Surakarta - Unzurna, Fitria; Darsinah, Darsinah; Rohmah, Wafrotur (CV. Rayyan Dwi Bharata, 2022)
This study aims to examine the planning, organization, implementation, and evaluation of the implementation of Biology learning in integrating 21st century skills at the Muhammadiyah High School Special Program for Kotatabarat Surakarta. This research is a qualitative research, with a case study research design. Data collection techniques in this study used observation, interviews, and documentation techniques. The data analysis technique in this study uses an interactive model analysis technique from Miles Huberman. The results of the study show that: a. Biology learning planning in integrating 21st century skills in SMA Muhammadiyah Special Program for Kotatabarat Surakarta begins with the creation of learning tools, namely: annual programs, semester programs, learning outcomes and learning objectives, as well as teaching modules; b. The organization of Biology learning in integrating 21st century skills at the Muhammadiyah High School Special Program for Kotatabarat Surakarta is contained in the teaching module; c. The implementation of Biology learning in integrating 21st century skills at the Muhammadiyah High School Special Program for Kotatabarat Surakarta consists of initial/preliminary activities, core activities, and closing activities; and D. Evaluation of the implementation of Biology learning in integrating 21st century skills at the Muhammadiyah High School Special Program for Kotatabarat Surakarta includes initial assessment, process, and summative or final assessment assessments. Management of Biology Learning in Integrating 21st Century Skills at SMA Muhammadiyah Special Program for Surakarta City is going well